Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Pegawai yang Dimediasi Kepuasan Kerja pada Pegawai Satuan Polisi Pamong Praja Kota Samarinda - Nina Maharani, Andi; Winarko, Ruddy; Indrawati, Mei; Febrita Sarie, Rena (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the influence of workload and work stress on employee performance through job satisfaction in employees of the Civil Service Police Unit. This study uses an explanatory research approach of quantitative methods. The research sample uses nonprobability sampling with a saturation sampling technique (census) through interviews and the distribution of questionnaires to all employees of the civil police unit in Samarinda City as many as 69 employees. Hypothesis testing using Smart PLS 4. The results of the study showed that the variable of work stress had no effect on the variable of job satisfaction of employees of the Samarinda City Pamong Praja Police Unit. The variable of work stress has a positive and significant effect on the variable of job satisfaction of employees of the Samarinda City Pamong Praja Police Unit.The variable of job satisfaction has a positive and significant effect on the performance variable of employees of the Samarinda City Pamong Praja Police Unit. The workload variable has no effect on the performance variable of the Samarinda City Pamong Praja Police Unit. The variable of work stress has no effect on the performance variable of employees of the Samarinda City Pamong Praja Police Unit. There was no effect on the workload variable on the employee performance variable through the employee satisfaction variable of the Samarinda City Pamong Praja Police Unit. There is an influence on the variable of work stress on the variable of employee performance through the variable of job satisfaction of employees of the Samarinda City Pamong Praja Police Unit.